Sexual Function and Related Factors in the Women with Urinary Incontinence Treated by Pelvic Floor Exercise - Damghanian M (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Urinary incontinence (UI) is a health problem which can affect women's sexual function. Pelvic floor exercise (PFE) is offered as a first-line therapy to women with UI. It has been shown that PFE might improve different dimensions of sexual function; however, few data is available on the sexual function and its related factors in the women with UI treated by PFE. Objectives: The present study aimed to determine sexual function and its related factors in the women with UI treated by PFE. Methods: This is a cross-sectional study on 183 married participants with confirmed UI treated by PFE in 2015-2016 using convenience sampling method in Imam Khomeini and Mohebe Yas urogynecology clinics. Data collection tools included demographic information, the Questionnaire for UI Diagnosis (QUID), Incontinence Severity Index (ISI), the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) and the Broom self-efficacy scale. Statistical analysis was run using univariate and multivariate linear regressions via STATA software. Results: The mean age of patients was 51.43±4.00 years, and the mean of sexual function according to PISQ-12 scale was 23.82±3.28 in women. The mean score of sexual function was less than the median of the scale score. Aging (p=0.018), retirement of husbands (p=0.044), being underweight (p<0.001), the history of abortion (p=0.036) and high self-efficacy in doing PFE (p<0.001) were found to be effective factors in sexual function. Conclusion: Modifiable factors included being underweight and having self-efficacy in performing PFE, which can be controlled using more management strategies to increase women's self-efficacy in doing PFE